Synthesis, electrochemical and optical studies of poly(ethylene oxide) based gel-polymer electrolytes for sodium-ion secondary batteries - Menisha, M.; Senavirathnage, Lahiru Niroshan Senavirathna; Vignarooban, K.; Iqbal, N.; Pitawala, H. M. J. C.; Kannan, A. M. (Solid State Ionics, 2021)
Sodium-ion batteries are being heavily investigated as cheaper alternatives to expensive lithium-ion batteries. However, synthesizing suitable electrolytes with sufficient ambient temperature ionic conductivities is a major bottleneck. In this work, gel-polymer electrolytes (GPEs) based on poly(ethylene oxide) (PEO) host polymer and NaClO4 ionic salt are developed by using ethylene carbonate (EC) and propylene carbonate (PC) plasticizer/solvent mixture. The optimized PEO:NaClO4:EC:PC composition (7:13:40:40 wt%) exhibits an ambient temperature ionic conductivity of 9.5 mS cm−1 and the variation of ionic conductivity with inverse temperature showed Arrhenius behavior with almost same activation energies for all the compositions. DC polarization studies on optimized composition reveals that the electrolyte is dominantly an ionic conductor (ti = 0.99) with negligible electronic conductivity (te = 0.01), which is highly desirable for an effective electrolyte. Cyclic voltammetric and linear sweep voltammetric studies confirm that the optimized composition is electrochemically stable for a voltage window of −1.85 to +1.85 V. Absence of any crystalline peaks in the X-ray diffractograms of the GPEs is a clear evidence for the amorphous nature of these GPEs. Broadening of the FTIR vibrational bands at 1000–1300 and 1700–1850 cm−1 is ascribed to the lowering of crystallinity resulting from the formation of PEO/Na+ complex through Na+ ion solvation by the polymer host. The GPE with optimized composition and highest ionic conductivity at ambient temperature is a suitable electrolyte for practical applications in sodium-ion batteries.
CRIS-Team Scopus Importer:2021-10-01
Keywords: DC polarization; Electrochemical impedance spectroscopy; Gel-polymer electrolytes; Ionic conductivities; Sodium-ion batteries